Measurement of Radon Concentration in College of Education for Pure Science / Ibn Al- Haitham Buildings Using CR-39 Detector - Salim, Duaa Abed; Ebrahiem, Sameera Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In the present work , radon concentration was measured indoor buildings in the College of Education for Pure Science/ Ibn Al- Haitham University of Baghdad using detector (CR-39) by counting track of alpha  resulting from decay series of uranium on the detectors which have exposure to air inside the rooms for (30) days , have been applied the equation (1) and (2) to calculate concentrations of Radon and the results showed that all samples were within the allowable range globally except two samples F1 and F2 where concentrations were (445.868Bq/m3) and (436.791Bq/m3) respectively , they were higher than allowable range globally which was (200-300) Bq/m3 recorded by (ICRP) [1] .